Nighttime Light Hurts Mammalian Physiology: What Diurnal Rodent Models Are Telling Us - Jorge Mendoza (Clocks & Sleep, 2021)
Natural sunlight permits organisms to synchronize their physiology to the external world. However, in current times, natural sunlight has been replaced by artificial light in both day and nighttime. While in the daytime, indoor artificial light is of lower intensity than natural sunlight, leading to a weak entrainment signal for our internal biological clock, at night the exposure to artificial light perturbs the body clock and sleep. Although electric light at night allows us “to live in darkness”, our current lifestyle facilitates nighttime exposure to light by the use, or abuse, of electronic devices (e.g., smartphones). The chronic exposure to light at nighttime has been correlated to mood alterations, metabolic dysfunctions, and poor cognition. To decipher the brain mechanisms underlying these alterations, fundamental research has been conducted using animal models, principally of nocturnal nature (e.g., mice). Nevertheless, because of the diurnal nature of human physiology, it is also important to find and propose diurnal animal models for the study of the light effects in circadian biology. The present review provides an overview of the effects of light at nighttime on physiology and behavior in diurnal mammals, including humans. Knowing how the brain reacts to artificial light exposure, using diurnal rodent models, is fundamental for the development of new strategies in human health based in circadian biology.